Mandatory Environmental, Social, and Governance (ESG) Disclosure: Legal Impact on Corporate Accountability in the Indonesian Stock Exchange - Imam Hanafi; Liu Yang; Li Na; Eka Anjani Sapitri (Yayasan Adra Karima Hubbi, 2025)
Background. Mandatory Environmental, Social, and Governance (ESG) disclosure has emerged as a regulatory mechanism intended to enhance transparency, strengthen corporate accountability, and align business practices with sustainable development goals in Indonesia. Purpose. This study aims to analyze how Indonesia’s evolving ESG regulatory framework influences corporate accountability among publicly listed companies on the Indonesian Stock Exchange (IDX). Method. A qualitative legal approach was employed, combining doctrinal analysis, regulatory mapping, and case-based examination of selected issuers to evaluate compliance patterns and the legal consequences of non-disclosure. Results. The findings demonstrate that mandatory ESG disclosure enhances procedural accountability, improves risk governance, and incentivizes firms to internalize sustainability practices; however, enforcement gaps and inconsistent reporting standards reduce its substantive effectiveness. Conclusion. The study concludes that mandatory disclosure contributes to stronger corporate accountability but requires clearer enforcement architecture, harmonized standards, and stronger supervisory capacity to achieve its intended regulatory impact.